Dimensional artefacts to achieve metrological traceability in advanced manufacturing. Issue 2 (2020) - Carmignato, S.; De Chiffre, L.; Bosse, H.; Leach, R.K.; Balsamo, A.; Estler, W.T.
Abstract: Dimensional measurements play a central role in enabling advanced manufacturing technologies, enhancing the quality of products and increasing productivity. This role becomes even more important in the context of Industry 4.0, where reliable and accurate digital models of products, processes and production systems are needed. To establish the traceability chain that links measurements in production to the length unit, dimensional artefacts – ranging from measurement standards to calibrated workpieces – are fundamental. The paper examines dimensional artefacts, discussing their characteristics, availability and role in supporting production by establishing metrological traceability, and provides guidelines for their selection, use and development.